Endovascular stent repair for a dissecting thoracoabdominal aneurysm is feasible in the setting of a district general hospital: a multidisciplinary approach. Issue 2 (1st August 2002) - Zaman, M J S; Carre, V; Parvin, S; Shepherd, D; Radvan, J
Abstract : A patient presented to a district general hospital with a type B dissection of the aorta. He was deemed too unwell for surgical intervention. An endovascular stent repair was successfully carried out. The case shows that such a procedure can be safely performed by a multidisciplinary team within a district general hospital.